The Tendency Of Co-Curriculum Students Towards Entrepreneurship Careers At Universiti Tun Hussein Onn Malaysia - Ismail, Nur Nadiah; Zakaria, Normah; Ab. Halim, Fazlinda; Masduki, Masadliahani; Yamin, Nor Azlin (Online Journal for TVET Practitioners, 2019)
Abstract: Due to the highly competitive job market, each student needs to have the readiness towards the entrepreneurship careers.  Students should be the â€˜job creatorsâ€™ and not the â€˜job seekersâ€™ that only wait for job offers after graduating. This study is to identify studentsâ€™ environmental factors in the tendency to become entrepreneurs and to identify the level of entrepreneurial readiness amongst the students. This descriptive study applies the non-experimental quantitative approach design. The respondents of this study consist of 73 co-curriculum students of Universiti Tun Hussein Onn Malaysia (UTHM) who enroll in the entrepreneurship club in which are drawn from a simple random selection. The result from the current study showed that students have the tendency to become entrepreneurs because they were willing to take the risks.  The result also showed that students have a medium level of tendencies towards the entrepreneurship careers. The Ministry of Higher Education (MOE), the university, lecturers, parents and the communities should give their co-operation to foster the awareness among the students that the entrepreneurship could be a career choice.